High Incidence of Cardiovascular Complications in Pheochromocytoma - Zelinka, T.; Petrák, O.; Turková, H.; Holaj, R.; Štrauch, B.; Kršek, M.; Vránková, A. B.; Musil, Z.; Dušková, J.; Kubinyi, J.; Michalský, D.; Novák, K.; Widimský, J. (Hormone and Metabolic Research, 2012)
Excess of catecholamines in pheochromocytoma is usually accompanied with classical symptoms and signs. In some cases, severe cardiovascular complications (e. g., heart failure, myocardial infarction) may occur. We performed a retrospective analysis focused on the incidence of cardiovascular complications (classified as follows: arrhythmias, myocardial involvement or ischemia and atherosclerosis, cerebrovascular impairment) before the establishment of diagnosis of pheochromocytoma among 145 subjects treated in our hospital. Cardiovascular complications occurred in 28 subjects, but these subjects did not differ significantly from subjects without complications in age, gender, body mass index, paroxysmal symptoms, symptom duration, tumor dimension, catecholamine secretory phenotype, and incidence of hypertension or diabetes mellitus. Arrhythmias occurred in 15 subjects (2 arrhythmia types in 2 subjects): atrial fibrillation in 9 subjects, supraventricular tachycardia in 3 cases, and ventricular tachycardia in 2 patients. Significant bradycardia was noted in 3 cases. Five subjects presented with heart failure with decreased systolic function (takotsubo-like cardiomyopathy found in 2 cases). One subject suffered from hypertrophic obstructive cardiomyopathy. Seven subjects presented with non-ST-segment elevation myocardial infarction, 2 patients with ST-segment myocardial infarction, and 1 subject underwent coronary artery bypass grafting. Two subjects suffered from significant peripheral atherosclerosis. Among cerebrovascular complications, transient ischemic attack was found in 3 cases, 2 subjects suffered from stroke, and subarachnoidal bleeding occurred in 1 patient. One subject suffered from diffuse neurological impairment due to multiple ischemic white matter lesions. These data show relatively high incidence of cardiovascular complications (19.3%) in subjects with pheochromocytoma. Early diagnosis is mandatory to prevent severe complications in pheochromocytoma.
Keywords: pheochromocytoma; paraganglioma; cardiovascular complications; catecholamines